Restoration of the Chesapeake Bay: lessons for other ecosystems - Batiuk, Richard A.; Blankenship, Karl; Boesch, Donald F.; Dennison, William C.; Harrison, Verna; Hershner, Carl; Hoagland, Roy A.; Horton, Thomas W.; Matuszeski, William; Miller, Thomas J.; Swanson, Ann P.; Todd, Albert H.; et al. (Frontiers in Marine Science, 2025)
With over 40 years of history, the multi-jurisdictional effort to restore the health of the Chesapeake Bay ecosystem has yielded some positive outcomes with water quality and natural resources showing measurable signs of improvement. The lessons learned from this multi-year, multi-jurisdictional restoration effort can provide understanding and guidance for ecosystem restoration efforts elsewhere. The 10 “lessons learned” from this effort, identified by a group of scientists and policy and program leaders whose experience in the Chesapeake Bay restoration spans its entire history, are that programs and practitioners should: 1) assure the presence and maintenance of strong and effective leadership; 2) be appropriately transparent everywhere and at all times, sharing both what is known and what is not known; 3) engage everyone, welcoming and encouraging participation from all; 4) secure long-term funding and support from multiple sources; 5) empower participation by seeking, soliciting, and using active participation from all voices; 6) use science to inform and confirm; 7) employ monitoring and modeling consistently and continuously in a manner that allows for ongoing improvement and evolution; 8) communicate conditions effectively and frequently, both good news and bad news; 9) be adaptable in incorporating new information and insights while maintaining clear, strong, and measurable goals and avoiding backsliding; and 10) ensure accountability, including mandatory action when voluntary action proves insufficient.